The Effect of Innovation of Infusion Installation Props on Clinical Skills in Midwifery Students at Medan Health Polytechnic of Ministry of Health - Ningsih, Tri Marini Supriarti; Mangunsong, Asryani Loveta (PT FORMOSA CENDEKIA GLOBAL, 2024)
Midwifery education is a vocational program with a curriculum consisting of 40% theory and 60% practice. Clinical skills involve health practitioners performing measurable actions on patients. Limited teaching aids, an unbalanced ratio of teaching aids to students, and expensive and complex infusion phantoms hinder efficient practicums. Innovation of modified infusion props can provide an alternative. This study aims to determine the effect of innovation of infusion props on clinical skills among second-year midwifery students who are familiar with infusion insertion. Using a pre-experimental design of one group pretest-posttest, 36 students were sampled through systematic random sampling. The infusion insertion checklist measured performance. The Wilcoxon test showed a significant increase (p = 0.001 <0.05), concluding that the innovation of infusion props had a positive impact on students' clinical skills.